Pope John Paul II and his Canonizations - Walsh, Michael J. (Studies in church history, 2011)
In his much quoted article ‘How to be a Counter-Reformation Saint’, Professor Peter Burke remarks on the ‘crisis of canonisations’ which afflicted the papacy in the middle years of the sixteenth century. That particular crisis, of course, was that there were no canonizations. As the veneration of saints came under attack from the reformers, successive pontiffs thought it politic to refrain from creating yet more. In the long pontificate of the late Pope John Paul II (1978—2005), the longest in papal history apart from that of Pope Pius IX (1846-78) — whom John Paul beatified, along with Pope John XXIII, on 3 September 2000 — there was another crisis of canonizations. In this instance, however, there were, in the eyes of some, far too many of them, devaluing the currency. Even the then Cardinal Josef Ratzinger was heard to utter words of disquiet. Indeed, John Paul’s saint-making policy was a topic almost as much for the secular press as the religious: ‘Catholicism turns to computers as the saints go marching in’ was the headline over a piece in The Sunday Times.